Experimenting with Living and Non-Living Nature - Qudratova Shaxnoza Baxtiyor qizi,; Doʻsanova Komila Qurbonboyevna, (American Journal of Biology and Natural Sciences, 2025)
This article analyzes the methods and significance of conducting experiments with living and non-living natural objects. Through such experiments, students and young researchers have the opportunity to observe the characteristics of living organisms, their growth, movement, and interaction with the environment. At the same time, studying non-living objects helps to understand natural laws, the properties of substances, and physical-chemical processes. In my opinion, such experiments develop scientific thinking and enhance students’ observation, questioning, and analytical skills.